1989
DOI: 10.2307/3577444
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Killing Chinese Hamster Ovary Cells Heated in G 1 : Effects on DNA Synthesis and Blocking in G 2

Abstract: To determine where in the cell cycle Chinese hamster ovary cells die following heating in G1, a mild hyperthermia treatment, i.e., 10 or 11.5 min at 45.5 degrees C, resulting in 40-50% cell kill was used. After a 7-14-h delay in G1, the cells heated in G1 eventually entered S phase and replicated all their DNA. Both an autoradiographic analysis with tritiated thymidine and a bromodeoxyuridine-propidium iodide bivariate analysis by flow cytometry revealed that both clonogenic and nonclonogenic cells were delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…In cells previously heated in G , for 10 min at 45.5"C, there was about a 12 hr delay in G I before they entered S phase. We found that the replicon initiation process was functional, the fork displacement rate had returned to a near normal rate, there was no increase in single-stranded regions in the replicating DNA, but there was still a similar delay in DNA chain elongation to complete inulticluster DNA molecules >120S in size [Wong et al, 1989a;Wong et al. 19931.…”
Section: Comparison With Heated Gi Cellsmentioning
confidence: 83%
See 1 more Smart Citation
“…In cells previously heated in G , for 10 min at 45.5"C, there was about a 12 hr delay in G I before they entered S phase. We found that the replicon initiation process was functional, the fork displacement rate had returned to a near normal rate, there was no increase in single-stranded regions in the replicating DNA, but there was still a similar delay in DNA chain elongation to complete inulticluster DNA molecules >120S in size [Wong et al, 1989a;Wong et al. 19931.…”
Section: Comparison With Heated Gi Cellsmentioning
confidence: 83%
“…To determine which of these four altered processes of DNA replication may be the critical step(s) in the induction process, we next investigated these same four processes in cells heated in G I , but now examined when they had entered S phase to replicate their DNA after a cell cycle block [Wong et al 1989a;Wong et al, 19931. Since heated G , cells do not die from the induction of chromosomal aberrations, any similarities or differences in these four S-phase altered processes between the 2 populations studied may help provide evidence as to which process is critical or required for the induction of aberrations.…”
Section: Comparison With Heated Gi Cellsmentioning
confidence: 99%
“…Depending on the length of exposure and the cell line being heated, hyperthermia may perturb the cell cycle, leading to an accumulation of cells in S and G 2 phase after heat exposure [Coss, 1986;Wong et al, 1989]. Interestingly, lamin B appears to be synthesized only in S phase [Foisy and Bibor-Hardy, 1988;Jost and Johnson, 1981].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the majority of cells were in the nonreplicative GI phase in this resistant period. Analysis of cell-cycle progression following a single -dose of hyperthermia revealed the blockage at GI, the most thermoresistant phase [28].…”
Section: Discussionmentioning
confidence: 99%